UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) TERHADAP PERTUMBUHAN Propionibacterium acne - Eka Kumalasari; Aina Aina; Noverda Ayuchecaria; Noor Aisyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Acne that appears can cause facial changes, in the form of swelling, redness, purulence and causing pain so that it will create an impression that is less attractive in appearance and affects one's beauty. One of the causes of acne is Propionibacterium acne. Dayak onion leaves are one of the plant that contain antibacterial compounds. The purpose of this study was to determine the antibacterial activity of ethanol extract of onion leaves on the growth of Propionibacterium acne.The antibacterial activity of this plant needs to be reviewed through with extract group with various concentrations, positive control group (clindamycin 0.1%) and negative control group (Aquadest). The results showed that the ethanol extract of dayak onion leaves had antibacterial activity against the growth of Propionibacterium acne. The diameter of the inhibition zone formed at concentrations of 20%, 40%, 60%, 80% and 100% respectively 7.25 mm (medium), 10.43 mm (strong), 15.23 mm (strong), 18, 55 mm (strong) and 22.20 mm (very strong).